Is macrocytic erythrocyte a new prognostic parameter in critical COVID-19 disease? - SOYLU, Veysel Garani; GÜLTEN, Sedat; YILMAZ, Ayşe; TAŞKIN, Öztürk; DEMİR, Ufuk; ÇATAN İNAN, Funda (Journal of Health Sciences and Medicine, 2021)
Introduction: In critical COVID- 19 patients, we aimed to examine the relationship mortality between the parameters and the macrocytic/microcytic erythrocyte population that are routinely evaluated in each patient admitted to the intensive care unit. Material and Method: It is a retrospective cross-sectional study and was conducted in Kastamonu University, Faculty of Medicine, a tertiary hospital intensive care units located in the North of Turkey .198 nonanemic critical COVID-19 patients treated between November 2020 and February 2021 were evaluated. The patients were divided into two groups as survival and non survival. Apache II score, saps II score and routine blood examinations of the patients were evaluated. Results: Among the groups; APACHE II score (p
Keywords: Health Care Administration; Macrocytic Erythrocyte Population; Intensive Care Unit; Covid 19; Complete Blood Count; Mortality; Sağlık Kurumları Yönetimi; 3. Good health